2012
DOI: 10.2138/am.2012.3977
|View full text |Cite
|
Sign up to set email alerts
|

Structural stability, cation ordering, and local relaxation along the AlNbO4-Al0.5Cr0.5NbO4 join

Abstract: (Al1–xCrx)3+Nb5+O4 (with 0 ≤ x ≤ 0.5) compounds have been investigated through the combination of X-ray powder diffraction (XRPD) and electronic absorption spectroscopy (EAS). In spite of the natural occurrence of AlTaO4, the lack of a mineral with composition AlNbO4 contrasts with the strong geochemical affinity between Nb and Ta elements. Rietveld refinements of XRPD data showed that the effective coordination numbers of the two non-equivalent octahedral sites (M1 and M2) in the AlNbO4 structure are much low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In a related recent study, M. Ardit investigated a series of (Al 1– x Cr x ) 3+ Nb 5+ O 4 (with 0 ≤ x ≤ 0.5) compounds by the means of X-ray powder diffraction and electronic absorption spectroscopy . The author confirmed that AlNbO 4 was indeed highly disordered and was able to deduce the occupation equation.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…In a related recent study, M. Ardit investigated a series of (Al 1– x Cr x ) 3+ Nb 5+ O 4 (with 0 ≤ x ≤ 0.5) compounds by the means of X-ray powder diffraction and electronic absorption spectroscopy . The author confirmed that AlNbO 4 was indeed highly disordered and was able to deduce the occupation equation.…”
Section: Resultsmentioning
confidence: 88%
“…According to Ardit, in AlNbO 4 , the proportion of aluminum satisfies the relation provided that Al M1 = Nb M2 .…”
Section: Resultsmentioning
confidence: 99%
“…In the alloy ZF6, both AlNbO 4 and CrNbO 4 were formed, while only the former was formed with Cr in solution in OHS1, which means that more Cr was present in the scale of ZF6 because there is incomplete solid solubility between AlNbO 4 and CrNbO 4 [68]. Indeed, up to some critical Cr content, the (Al,Cr)NbO 4 is one phase with the structure of AlNbO 4 (monoclinic, C2/m space group) compared with two phases AlNbO 4 plus CrNbO 4 (tetragonal (rutile type structure), P42/mnm) when the critical Cr concentration is exceeded, in which there is no structural relaxation [68].…”
Section: Oxide Scalesmentioning
confidence: 99%
“…Figure 3 shows the enthalpy difference between all of the structures considered in the calculations. They include not only all of the previously known polymorphs but also the new FeVO 4 -I′ polymorph, a monoclinic structure described with the same space group as that of FeVO 4 -II′ but with different unit-cell parameters, 21 and a triclinic structure that is a distortion of FeVO 4 -II′. We used for the last two structures the names FeVO 4 -II″ and FeVO 4 -I″, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To obtain this polymorph in addition to pressure, a temperature of 800 °C has to be applied . This indicates that there is a large kinetic barrier blocking the transition from FeVO 4 -I to FeVO 4 -II.…”
Section: Results and Discussionmentioning
confidence: 99%